Viskositas dan densitas energi pada susu pisang probiotik dengan rancangan acak lengkap - Ramdika, Sari Bema; Sari, Desri Maulina; Ramadhani, Ira Dewi; Prautami, Erike Septa (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background Probiotic banana milk is a product containing potassium from Ambon Banana developed to address gastrointestinal motility issues in surgical patients. However, two important parameters to be considered for surgical patients are viscosity and energy density.Objectives: To analyze the viscosity and energy density of probiotic banana milk and its potential as a nutritional intervention for surgical patients.Methods: This study employed an experimental design with a Completely Randomized Design (CRD) with 3 treatments and 3 replications in laboratory test. The treatment in this study was to differentiate the proportion between Green Ambon Bananas (Musa acuminata colla) and starter before cooking, which was divided into 3 formulations. Viscosity measurement was assessed using a digital viscometer NDJ-5 (Vevor, Shanghai, China) according to the manufacturer's recommendations. The energy density of probiotic banana milk was measured using the energy ratio formula [kcal] to weight (g). Energy density data were analyzed using ANOVA test.Results: The results showed that both the highest viscosity and density were in F3 (1630 m.pa.s with 0,35 kcal/g) and the lowest was in F1 (472 m.pa.s with 0,31 kcal/g). The ANOVA test showed a difference in energy density in the three formulations with a p-value of 0,003. The results of the post-hoc test showed that there was a difference between each formulation (F1 and F2; F1 and F3; F2 and F3).Conclusion: Sample F3 has the highest viscosity and energy density compared to F1 and F2, so it has the highest potential to be given to pre-and post-surgical patients to help speed up the recovery process.